Magnetic resonance angiography in giant cell arteritis: results of a randomized controlled trial of tocilizumab in giant cell arteritis. (23rd February 2018) - Reichenbach, Stephan; Adler, Sabine; Bonel, Harald; Cullmann, Jennifer L; Kuchen, Stefan; Bütikofer, Lukas; Seitz, Michael; Villiger, Peter M
Abstract: Objective: To analyse magnetic resonance angiographic (MRA) vessel wall signals from a randomized controlled trial of tocilizumab (TCZ) to treat GCA. Methods: Participants were assigned in a 2:1 ratio to receive either TCZ + glucocorticoids (GCs) or placebo + GC infusions at 4-week intervals for 52 weeks. GCs were started at 1 mg/kg/day, then tapered to 0.1 mg/kg/day at week 12 and thereafter down to zero. Patients with initial positive MRA findings underwent control MRA at weeks 12 and 52. Vessel wall signals were scored from 0 (normal) to 3 (intense late enhancement). Outcomes were the number of patients with complete MRA remission at weeks 12 and 52, and changes in vasculitis score, vessel anatomy and atherosclerosis. Results: Of the 30 randomized participants, nine TCZ and two placebo patients had no vessel wall enhancement on initial MRA. At week 12, MRAs were performed in nine TCZ and four placebo patients (nine and three in clinical remission, respectively). Three (33%) TCZ patients showed normalization of vessel wall signals compared with one (25%) placebo patient. At week 52, there was additional MRA improvement in some TCZ patients, but one-third showed persistent or increased late vessel wall enhancement. There was no formation of aneurysms or stenosis and no increase in atherosclerosis. Conclusions: Although TCZ resulted in complete clinical and laboratory remission of GCA over 52 weeks, MRA signals in vessel walls normalized in only one-third of patients. Whether these signals are of prognostic importance remains to be determined.